\(\begin{array} {} (A): & 2016 = 1 + 2 + 3 +\cdots+ 62 \\ (B): & 2016 = \sqrt{1^3 + 2^3 +\cdots+ 63^3} \\ (C): & 2016 = 2^{10} + 2^9 +\cdots+ 2^4 \\ (D): & 2016 = 1^2 - 2^2 + 3^2 - 4^2 +\cdots-62^2 + 63^2 \end{array} \)
Consider the statements above.
Then,
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution, sir.
The D can also be evaluated more easily by using a 2 − b 2 = ( a + b ) ( a − b ) which can be written as − 1 − 2 − 3 − 4 − . . . − 6 1 − 6 2 + 6 3 2 = 6 3 2 − 3 1 × 6 3 = 6 3 × 3 2 = 2 0 1 6
Log in to reply
You are right. I have edited your comment into LaTex. You can check to see how it is done by clicking Edit.
C = 2 0 3 2 and not 2 0 3 1
Problem Loading...
Note Loading...
Set Loading...
A B C D = 1 + 2 + 3 + ⋯ + 6 2 = n = 1 ∑ 6 2 n = 2 6 2 ( 6 3 ) = 1 9 5 3 = 2 0 1 6 = 1 3 + 2 3 + 3 3 + ⋯ + 6 3 3 = n = 1 ∑ 6 3 n 3 = ( 2 6 3 ( 6 4 ) ) 2 = 2 0 1 6 = 2 1 0 + 2 9 + 2 8 + ⋯ + 2 4 = 2 4 n = 0 ∑ 6 2 n = 2 − 1 2 4 ( 2 7 − 1 ) = 2 0 3 2 = 2 0 1 6 = 1 2 − 2 2 + 3 2 − 4 2 + ⋯ − 6 2 2 + 6 3 2 = n = 1 ∑ 6 3 n 2 − 2 ( 2 2 ) n = 1 ∑ 3 1 n 2 = 8 5 3 4 4 − 8 ( 1 0 4 1 6 ) = 2 0 1 6
Therefore, both (B) and (D) are true .